EVALUASI PELAKSANAAN PERATURAN DAERAH NOMOR 4 TAHUN 2016 TENTANG RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH KABUPATEN PONOROGO TAHUN 2016-2021 DI DESA DAYAKAN KECAMATAN BADEGAN KABUPATEN PONOROGO TAHUN 2019: (Studi Kasus Pelaksanaan Program Bantuan Pangan Non Tunai) - Moh. Gufron Rosyid Ridlo (JI@P, 2021)
The results showed an evaluation of the implementation of Non-Cash FoodAssistance (BPNT) using William Dunn with six variables, namely effectiveness,efficiency, adequacy, leveling, responsiveness and accuracy, namely: BPNTimplementation starts from the stages of registration or account opening, educationand socialization. , distribution, and purchase of goods at e-warong and Bank BNI46. Achievement of BPNT implementation results, seen from BPNT objectives, isstill not optimal for all BPNT KPM. The assessment of the implementation of BPNTin Dayakan Village, Badegan District, Ponorogo Regency based on William Dunn'stheory is the effectiveness of achieving BPNT goals, efficiency of distribution timeand the number of e-warongs or BNI 46 agents who facilitate the purchase of goods,criteria for the leveling of BPNT program recipients, and responsiveness criteriafor problem handling not good. Meanwhile, the criteria for the adequacy of theresults / benefits of BPNT that are felt by the poor to meet food needs and thecriteria for BPNT's accuracy in answering the problems of poverty and hungerfaced by the poor are quite good.Keywords: effectiveness, efficiency, adequacy, leveling, responsiveness andresponsive